PERANAN MEDIA KOMIK TERHADAP LITERASI SAINS SISWA SD KELAS V PADA MATERI DAUR AIR (PENELITIAN PRE-EXPERIMENTAL TERHADAP SISWA KELAS V SD KECAMATAN PASEH KABUPATEN SUMEDANG) - Nursholihat, Khoerunnisa; Sujana, Atep; Karlina, Dety Amelia (Jurnal Pena Ilmiah, 2017)
In Indonesia , student ability of science literacy is still not optimal. This is known from the fact that obtained based on the latest PISA survey result in 2015. The score of Indonesian student science literacy ability is below the average of international score. Indonesia obtain 403 score, while the average of international score is 500. Depart from this problem, designed comics â€œHari Ini Hujanâ€ as a medium of science learning. This research uses pre-experimental design type one group pretest-posttest design, with fifth grade students of SDN Paseh I, Paseh II and Legok I as sample. The research instrument used test of science literacy, self-assessment questionnaire and teacher performance observation. Obtained P-value (Sig.2-tailed) = 0,000 from test the difference of two averages which mean that comics â€œHari Ini Hujanâ€ can improve fifth grade student ability of science literacy on the water cycle study.